Nekateri vidiki terenskih preskusov peltonovih turbin v HE "Perućica" - Mrkić, Milo (Strojniški vestnik, 2002)
This paper describes the basic power parameters of the "Perućica" HEPP. Also included is an analysis of the work process in the Pelton turbine and an experimental-analytical method for determining the nozzle-flow characteristics under real working conditions.
Keywords: turbine Peltonove; parametri energetski; karakteristike procesov; metode eksperimentalne; Peltonove turbine; delovne karakteristike; eksperimentalne metode; hidroelektrarne